The S Protein of Group B Streptococcus Is a Critical Virulence Determinant That Impacts the Cell Surface Virulome - Campeau, Anaamika; Uchiyama, Satoshi; Sanchez, Concepcion; Sauceda, Consuelo; Nizet, Victor; Gonzalez, David J. (Frontiers in Microbiology, 2021)
Group B Streptococcus (GBS, S. agalactiae) is a human commensal and occasional pathogen that remains a leading cause of neonatal sepsis and meningitis with increasing disease burden in adult populations. Although programs for universal screening in pregnancy to guide intrapartum prophylaxis have reduced GBS invasive disease burden resulting from mother-to-newborn transfer during birth, better knowledge of disease mechanisms may elucidate new strategies to reduce antibiotic exposure. In our efforts to expand the knowledge base required for targeted anti-virulence therapies, we identified a GBS homolog for a recently identified virulence determinant of group A Streptococcus, S protein, and evaluated its role in GBS pathogenesis. A GBS S protein deletion mutant, ess, showed altered cell-surface properties compared to the WT parent strain, including defective retention of its surface polysaccharide. Quantitative proteome analysis of enzymatically shaved surface epitopes of the GBS ess mutant revealed a dysregulated cell surface virulome, with reduced abundance of several protein and glycoprotein components. The ess mutant showed markedly attenuated virulence in a murine model of GBS systemic infection, with increased proteasome activity detected in the spleens of animals infected with the ess mutant. These results expand the key roles S protein plays in streptococcal pathogenesis and introduces a new GBS virulence determinant and potential target for therapy development.